Historical Dictionary of Figure Skating. - Hines, James R. (Rowman & Littlefield Pub. Group, 2011)
Figure skating is the most popular televised sport at the Olympic Winter Games and is the oldest of the winter sports, having first been contested at the Games of the fourth Olympiad in London in 1908. No other sport creates such a perfect balance betweenathleticism and artistry, and the athletes--many of them household names like Oksana Baiul, Brian Boitano, Nancy Kerrigan, Evan Lysacek, Katarina Witt, and Kristi Yamaguchi--spend years in training to make it look effortless. The Historical Dictionaryof Figure Skating relates the history of the sport through a chronology, an introductory essay.